Esqueleto interactivo - Abrahams, P. H. (Peter Herbert); Sanudo, J. R.; Mirapeix, R. M. (London : Primal, 1999)
Features a three-dimensional human skeleton, showing in computer graphics ev muscle attachment, and landmark. Contains additional software which allows tea slide presentations, design customized course material, produce customized qui out high definition images
Title from disc label
CD is available at Koleksi Media, Perpustakaan HUKM
Keywords: Human skeleton